O mercado do livro didático no Brasil: da criação do Programa Nacional do Livro Didático (PNLD) à entrada do capital internacional espanhol (1985-2007) - Cassiano, Célia Cristina de Figueiredo (2007)
This work presents the results of two decades of implementation of the Programa Nacional do Livro Didático (National Textbook Program) PNLD, in Brazil. Created in 1985 as an integral part of the education policy of a country undergoing a process of redemocratization. The work relates also the alterations that happened in the in the Brazilian textbook market during this period: from the concentration of family-run publishing houses by the end of the XX century to the present oligopoly of large entrepreneurial groups. Since 1995, in the light of the reforms implemented by Fernando Henrique Cardoso s government (1995-2002), substantial modifications are made in the PNLD, and, at the same time, large Spanish publishing houses that were by then strongly settled in Latin American and Caribbean countries establish themselves in Brazil, mainly as a result of the opening of economic policies to international capital implemented during this period. Thus, I scrutinize the insertion of Brazil into this Iberian-American textbook market and the entrance of Spanish groups into our country, whith has above all amalgamated cultural and educational elements, particularly when one takes into consideration the insertion of the Spanish language into the official curriculum of Brasilian schools, fostered both by the government and the Spanish entrepreneurs. Research tools utilized include a bibliographic survey of the legislation pertinent to the subject, diversified newspaper and magazine reports, publications made by the representatives of the Brazilian and Spanish publishing markets, and government documents, including economic field studies carried on in both Brazil and Spain, where part of my research was conducted. My primary objective is to turn explicit the fact that global processes linked to the politic and economics of the global textbook market though extrapolating school boundaries, suffer market constraints. Said contraints implicitly guide curriculum development. My analytical approach stems from a critical curriculum theory, and Michael W. Apple and J. Gimeno Sacristán are theoretical cornerstones that support this premise